Importance of studies on animal aging processes in the search for means to prolong human life (III. Cellular Thoeries; Hormones and Enzymes - ΧΑΤΖΗΟΛΟΣ ΒΑΣ. K. (Journal of the Hellenic Veterinary Medical Society, 2019)
This paper ties in the previous analysis concerning cell culture properties, DNA damage and repair, protein synthesis and degradation, etc., with the current hypothesis on the causes of aging, including the possibility of amaurosis in genetic transcription or redundancy in genetic information; the reduction of the mumber of DNA replications and that of ribosomes; the templates for protein synthesis; the hardening of the crosslinkages of the DNA double-stranded helix and the role of free re die als; the accumulation of lipofuchsin in the cells; and, finally, the general cellural aging clock theory. However, since factors based only on cell genetic concepts cannot explain all of the phenomena occurring during aging, additional hypothesis proposed by various researchers based on endocrinological observations are presented herein. It is evident from the vital role of the various hormones in the regulating of physiological processes that one or more endocrine glands, depending on the neurohumoral system, contribute in some way to the process of aging. As is well known, the thymus, with its hormones and hormonal factors, is considered by many to be the principle gland involved in aging. Thymosine, its hormone, is known to be active in protecting the organism against infection, enhancing immunity against cancer, accelerating rejection of grafts, and, generally, improving the immunity function of those suffering from congenital immuno-deficlencies and other similar conditions. However, other researchers maintain that the thyroid is the principle gland regulating the aging processes. It is a fact that this gland, in response to signals from the hypophysis, mediates the central endocrine changes involved in aging and the autonomic mechanism of the endocrine functions. Furthermore, thiroxine is believed to play a vital role in the functions of all cells and tissues, in addition to controlling metabolic rate. Its deficiency, hypothyroidism, produces disturbances and changes similar to those observed in aging, as well as promoting susceptibility to heart attack; whereas its removal often leads to atherosclerosis in both animals and man. With aging, the hypophysis, through the thyroid, produces a slowing down of the metabolic rate by the release of the DECO of death hormone. This progressive decline of the metabolic rate with age can be restored to juvenile levels in old rats by removing the hypophysis and injecting thyroid hormones. Also included in this discussion is the possibility that the adrenals, and presumably other endocrine glands, are responsible for the steadily progressing changes which take place in the brain during aging. This view stems from the similarity of these changes to those in young persons suffering from the Cushing syndrome which, as generally known, is manifested by premature aging and preceded by the circulation of adrenal hormones at high levels. With respect to hormonal function, the reader is reminded that this function is carried out only when the specific type of cell is ready to receive the message earmarked for it, a condition determined by the number of active receptors contained by the cell and by hormone binding capacity. This capacity decreases significantly with age in many tissues.